The impact of the blended learning strategy for outstanding performers in learning the skills of sending and receiving volleyball for students - muthnaa alqurary; ِAmira Moneer (College of Physical Education and Sport Sciences, 2023)
The aim of the research is to identify the impact of the blended learning strategy for those with outstanding performance in learning the skills of transmitting and receiving volleyball for students, as well as knowing the preference in the effect between the two groups (experimental and control). (I used with it the strategy used by the teacher) on a homogeneous sample of fifth preparatory students, numbering (24) students, who were chosen through the two measures of distinguished motor performance for the skills of sending from above (tennis) and receiving from the bottom of the research community consisting of (150) students After excluding a number of students in the School of Literary Newspapers for Boys in Baghdad Governorate - Al-Karkh II, the two skills of forwarding facing from the top (tennis) and receiving transmissions from the bottom were chosen by the researchers, and they conducted the exploratory experiment on a sample of (10) students from (with distinguished motor performance ) for the two aforementioned skills from the research community and from outside the research sample, they were chosen through the two measures of distinguished motor performance for these two skills, then they conducted pre-tests to ensure the equivalence of the two groups, to start with the main experiment from one starting point, and after applying the educational units amounting to (12) educational units at an average One educational unit per week for each group, after which the post-tests were conducted under the same conditions as the pre-tests. After processing the data statistically, the two researchers reached the most important conclusions: There is a positive effect (of the blended learning strategy) and (the strategy used by the teacher) in learning the skills of sending from above (tennis) and receiving from below in volleyball in the research sample, in varying proportions. There is a preference for blended learning strategy over the strategy used in learning these two skills.